ONIGIRI SORGUM TUNA BALADO (OSTUDO) SEBAGAI MAIN COURSE RENDAH GLUTEN PENGGANTI BERAS - Sutriyati Purwanti, Ainun Tina Kesti (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to 1) Find the right recipe for making Ostudo (Onigiri Sorghum Tuna Balado) 2) Knowing the community’s acceptability of Ostudo Products (Onigiri Sorghum Tuna Balado) 3) Knowing the nutritional content found in Ostudo products. The type of research used is R & D (Research and Development) with a 4D development model (Define, Design, Develop, Disseminate). The place and time of the study are the Food Laboratory of the Department of Food and Clothing Engineering Education, Faculty of Engineering, Yogyakarta State University, starting from February to April 2019. The results of this study are: 1) The right recipe for making Ostudo by 75%. A special technique that must be done is to soak sorghum rice first. 2) The results of the acceptance of the limited scale test of the reference product are indicated by the average yield of 3.48 while the development product is 3.58. The level of wide-scale acceptance is indicated by the overall results of 3.8. 3) Based on the proximate test results the highest content is found in the water content with the results of 61.21% and the smallest is the ash content with a yield of 0.27%. Keywords: Sorghum rice, Ostudo, proximate test, technique